Relationships Between Learning Achievement, Self-Monitoring , Cognitive Style, and Learning Style in Medical Students (2016)
An analysis is presented of the relationships that exist between learning achievement, the use of metacognitive self-monitoring, cognitive style (Field Dependence-Independence dimension), and learning style (Grasha’s Classification) in university students. The study was conducted with a population of 130 medical students enrolled from 6th to 10th semester in a university in Bogotá, Colombia. Using a bivariate correlation,associations were sought between the Grade Point Average (GPA) achieved by students, metacognitive self-monitoring, which was measured with the Motivated Strategies for Learning Questionnaire (MSLQ), cognitive styles, which were measured through the Embedded Figures Test (EFT), and learning styles as reported in the Grasha inventory. Findings showed positive correlations between learning achievement and the variables: cognitive style, use of metacognitive strategies, and participantand competitive learning styles, while negative correlations were found with avoidant and dependent learning styles. Similarly, other correlations were found between the studied variables, which are discussed in the document.